A digital framework for metrological information. (December 2021) - Xiong, XingChuang; Zhu, Yiwei; Li, Jinyuan; Duan, Yuning; Fang, Xiang
Abstract: A digital-system structure is very important for developing Metrology for Digital Transformation (M4DT) at NMIs. A plan for the digital transformation in metrology at the National Institute of Metrology (NIM), China is proposed. The plan includes the digitalization of metrology standards, measuring instruments, metrological information, and metrological activities. Among them, the Digitalization of Metrological Information (DMI) is the key as a link between digital components and hence its development is a high priority. In order to realize a comprehensive DMI, a multi-layered, modular digital framework for structured information is designed, including a traceable chain of metadata models for metrological information, conversion and verification software libraries, and a supporting digital infrastructure. It provides an option for NMIs to implement digital transformation.